Transforming Indigenous Local Operator Competencies Toward Automation-Based Operations in Underground Mines: A Case Study of PT Freeport Indonesia's GBC Mine - Rogate Saragih; Achmad Ghazali (Green Publisher Indonesia, 2026)
The accelerated adoption of Industry 4.0 in underground mining has created a significant gap between mandated automation and local workforce readiness, particularly among indigenous Papuan workers with limited technological exposure. This study examines the competency gap dynamics among haulage operators at PT Freeport Indonesia's Grasberg Block Cave (GBC) Mine using a mixed-method approach based on Soft Systems Methodology (SSM). Survey analysis of 30 respondents reveals that technical competency for remote operations is at a moderate level (mean= 3.37), significantly different from the high level of learning readiness (mean= 4.33). A group of operators from seven indigenous Papuan tribes recorded the lowest technical competency score (mean= 2.55) but demonstrated strong learning readiness (mean= 4.18). Triangulation of quantitative data, in-depth interviews, and secondary operational data confirms that the primary barriers were not motivation or safety awareness, but rather limitations in the capability development architecture: limited time for structured practice, limited mentoring capacity, and the absence of pre-employment pathways tailored to the sociocultural backgrounds of local communities. Analytic Hierarchy Process (AHP) was used to prioritize five strategic alternatives, with the highest results in Precision TNA and andragogy-based training redesign (score 0.368), followed by a 4-level remote training program with habit formation architecture (score 0.317), and the establishment of the 7 Papuan Tribe Pre-Mining School (score 0.204) as a long-term structural solution. These findings contribute to the literature on socio-technical systems management, local workforce integration in high-risk industries, and the application of andragogy in the context of digital transformation in developing countries.